AGAMA PERSPEKTIF SYED MUHAMMAD NAQUIB AL-ATTAS - Miftahul Jannah; Moh. Zaiful Rosyid; Syarifuddin; Hikmatu Ruwaida; Mauizdati, Nida (Institut Agama Islam Darul Ulum Kandangan, 2021)
The idea of Islamization of Naquib Al-Attas is basically its intellectual response to the negative effects of modern (Western) science. The concept of reality or worldview is inherent in every science, which then spreads to epistemological issues. The idea of Islamization of science was born along with the various downturns and inequalities that colored the lives of humanity due to the separation of knowledge from religion. Religion which is considered to have a central role in life needs to get more attention considering religion influences the formation of human personality. The ultimate goal of religion for humans is to return man to his former state by involving the search for his final identity and destiny through righteous deeds (good deeds).singkat.